1983
DOI: 10.3181/00379727-173-41637
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Nephron Sodium and Potassium Reabsorption in Newborn and Adult Dogs during Saline Expansion

Abstract: Abstracf. Studies were camed out in 23 anesthetized neonatal dogs aged 2 to 20 days and in 16 adult dogs to compare the effects of saline volume expansion on renal tubular Na and K reabsorption between newborn and adult animals. Proximal-and distal-tubule function was estimated by the distal-nephron-blockade technique using ethacrynic acid and amiloride. During saline infusion, which increased extracellular volume by approximately 30% for both age groups, total nephron fractional Na reabsorption was 0.91 for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Interestingly, patients carrying KCNJ1 mutations may show hyperkalemia as an initial sign of the disease, soon after birth; then, this defect is even reversed [8]. Micropuncture [9] and clearance [10] studies in young rats have demonstrated limited ability in K + secretion compared with adults. Accordingly, in microperfused CCD from mammalians, K + secretion is low in newborns and cannot be stimulated by tubular flow [11].…”
Section: Hypokalemia: Lessons From the Salt-losing Tubulopathiesmentioning
confidence: 99%
“…Interestingly, patients carrying KCNJ1 mutations may show hyperkalemia as an initial sign of the disease, soon after birth; then, this defect is even reversed [8]. Micropuncture [9] and clearance [10] studies in young rats have demonstrated limited ability in K + secretion compared with adults. Accordingly, in microperfused CCD from mammalians, K + secretion is low in newborns and cannot be stimulated by tubular flow [11].…”
Section: Hypokalemia: Lessons From the Salt-losing Tubulopathiesmentioning
confidence: 99%
“…This greater avidity of the distal nephron when distal delivery is increased is also observed when distal sodium and chloride delivery are increased (7,32) and thus is probably common to more than one segment of the distal nephron. The factors responsible for this greater propensity for electrolyte reabsorption when delivery is increased cannot be determined from these studies.…”
Section: Discussionmentioning
confidence: 81%
“…It is difficult to identify a single factor that could effect the reabsorption of these electrolytes in different segments. It should be noted that reabsorption of sodium, chloride, and bicarbonate per g kidney are much lower in the newborn than in the adult under all of these experimental conditions, even though the fractions of the distal loads reabsorbed are higher, because the distal loads are much lower as a result of a lower GFR per g kidney in the newborn (7,32). Thus, even if the reabsorptive capacities per g kidney of these segments of the immature distal nephron were less than those ofthe mature distal nephron, it is possible that these capacities might be exceeded in the adult but not in the newborn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations